In Search of Heterotopia Religiosity? Motives for Religious Tourism and Pilgrimages to Zion Christian Church Mbungo Shrine: A Case from Zimbabwe - Muzurura, Joe; Mutambara, Emmanuel; Mahohoma, Takesure (Africajournals, 2022)
Religious tourism and pilgrimage are theocentric terms that refer to people visiting holy and sacred shrines seeking; God’s indulgence and absolution of sins in the afterlife, spiritual and physical healing, regeneration of the soul and spirit, acquiring new religious and cultural experiences, a shorter stay in the purgatory and a transcendence of one’s former frame of reference. Religious tourism and pilgrimage have a strong potential to: create quality employment opportunities, increase local community resilience against poverty, curtail rural flight migration, foster mutual understanding, respect, peace and harmony among tourist, pilgrims, local communities, and even countries, and importantly may contribute to rapid national growth and development. The study used a multiple paradigm approach to investigate motives for visiting ZCC Mbungo Shrine in Zimbabwe by religious tourists and pilgrims. Data was collected using representative focus group made up of 10 participants and revelatory focus group consisting of 5 participants. Our findings show that religious tourists and pilgrims to ZCC Mbungo Shrine are motivated by the quest for spiritual and physical healing, new cultural experiences, piety, religious affiliation and veneration of the founding member. The study recommends improving tourist facilitating conditions, promotion of eco-tourism and cultural tourism alongside religious tourism and pilgrimages to the shrine